2021
DOI: 10.1021/acs.accounts.1c00285
|View full text |Cite
|
Sign up to set email alerts
|

Data Science Meets Physical Organic Chemistry

Abstract: Metrics & MoreArticle Recommendations CONSPECTUS: At the heart of synthetic chemistry is the holy grail of predictable catalyst design. In particular, researchers involved in reaction development in asymmetric catalysis have pursued a variety of strategies toward this goal. This is driven by both the pragmatic need to achieve high selectivities and the inability to readily identify why a certain catalyst is effective for a given reaction.While empiricism and intuition have dominated the field of asymmetric cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 65 publications
0
66
0
Order By: Relevance
“…At the outset of the investigation, preliminary experimental data indicated that monophosphine ligands effectively promoted a nickel(0) cross-coupling of enol tosylate 1a and pinacol boronate 2a to access representative tetrasubstituted alkene diastereomers 3aa (Figure A, see Supporting Information for details). To further streamline efforts toward developing a ligand-controlled diastereoconvergent transformation, a data-rich optimization approach was envisaged wherein chemical space analysis would guide high throughput experimentation (HTE). , The kraken organophosphorus­(III) descriptor library, which contains >190 conformationally relevant molecular descriptors for 1558 monodentate phosphorus ligands, was employed for this purpose . The dimensionality of the descriptors for commercially available phosphine ligands within the library was reduced using principal component analysis (PCA) .…”
Section: Resultsmentioning
confidence: 75%
“…At the outset of the investigation, preliminary experimental data indicated that monophosphine ligands effectively promoted a nickel(0) cross-coupling of enol tosylate 1a and pinacol boronate 2a to access representative tetrasubstituted alkene diastereomers 3aa (Figure A, see Supporting Information for details). To further streamline efforts toward developing a ligand-controlled diastereoconvergent transformation, a data-rich optimization approach was envisaged wherein chemical space analysis would guide high throughput experimentation (HTE). , The kraken organophosphorus­(III) descriptor library, which contains >190 conformationally relevant molecular descriptors for 1558 monodentate phosphorus ligands, was employed for this purpose . The dimensionality of the descriptors for commercially available phosphine ligands within the library was reduced using principal component analysis (PCA) .…”
Section: Resultsmentioning
confidence: 75%
“…While single and multivariate linear regressions are powerful tools for understanding and correlating experimental data [ 11 ], these approaches tend to only represent gradients of chemical reactivity but do not describe the implicit complex reaction surface. Non-parametric algorithms are typically invoked in modeling complex relationships and have seen increasing use in electrochemistry [ 7 , 10 , 30 32 ].…”
Section: Data-drive Approaches For Electrochemical Reaction Optimizationmentioning
confidence: 99%
“…An additional curation step was found necessary to produce statistically robust linear models based on the hypothesis that disparate ligand types may impart selectivity through unique mechanisms. 42 As the training set was diverse, interrogation of the chemical space revealed a group of ligands which occupied a position in chemical space remote from the remainder of the ligands evaluated (see SI Fig. S14).…”
Section: Multi-objective Optimizationmentioning
confidence: 99%